The Effectiveness of Bioremediation Using Indigenous Bacteria for the Removal of Heavy Metals from Contaminated Soil - Salman, Russell Daoud; Al-Shabaki, Haider Muhammad Ali; Mohammed, Alaa Nema; Mohammed, Wijdan merzah abdulhussein; Wanas, Zahraa Hussein (American Journal of Biology and Natural Sciences, 2025)
The impact of heavy metals on health, flora, fauna, and soil fertility is enormous. Several researchers have focused on the use of various strains of bacteria to assess their potential for bioremediation of heavy metal contaminated soil. Most of them have used non-indigenous bacteria in their study for the bioremediation of heavy metals. Bacteria isolated from heavy metal contaminated soil are expected to show higher tolerance and suitable to be used for the bioremediation of heavy metals. The present review aims at emphasizing the recent developments on the bioremediation of heavy metal contaminated soils using indigenous bacteria.